International responsibility for the proliferation of small arms and light weapons - عبد الامير رفاه نجاح; خلف حسام عبد الامير (Journal of Legal Sciences, 2021)
he responsibility system has an important role in various international fields, including the area of ​​the proliferation of small and light weapons, and the destabilization and imbalance that this proliferation causes causes and legal centers, because without them, the agreement rules have no impact and significance, given the guarantees decided by the responsibility to ensure respect for the obligations imposed by that system, Every action that violates the provisions of international law, whether it comes to a simple violation of an international obligation or a violation of a fundamental obligation that affects the interests of the international community requires the accountability of its perpetrator, and as a result of this breach the state is responsible for removing the damage and compensating the affected people with respect to the state of Affected.